The Estimation of Price Sensitivity Curves Using Generalized Linear Models - Hari Wijayanto; Khairil A. Notodiputro; . Barizi; Jajah K. Wagiono (Forum Pasca Sarjana, 1995)
The estimation of price sensitivity curves is usually based on historical data of the product. The estimates obtained, however, are potentially biased especially if the previous condition does not reflect the current market situation. alternativety, the estimation could be based on preference data. This paper introduces the use of Generalized Linear models to estimate the curve based on preference data.